Assessing the potential for nevirapine removal and its ecotoxicological effects on Coelastrella tenuitheca and Tetradesmus obliquus in aqueous environment. (15th January 2023) - Reddy, Karen; Renuka, Nirmal; Kumari, Sheena; Ratha, Sachitra Kumar; Moodley, Brenda; Pillay, Kriveshin; Bux, Faizal
Abstract: Remediation of the antiretroviral (ARV) drug, nevirapine (NVP) has attracted considerable scientific attention in recent years due to its frequent detection and persistence in aquatic environments and potential hazards to living organisms. Algae-based technologies have been emerging as an environmentally friendly option for the removal of pharmaceutical compounds, but their ARV drug removal potential has not been fully explored yet. This study aimed to explore the ecotoxicity and removal potential of NVP by two microalgal species, Coelastrella tenuitheca and Tetradesmus obliquus . Lower environmental concentrations (up to 200 ng L −1 ) of NVP enhanced the microalgal growth, and the highest dry cell weight of 941.27 mg L −1 was obtained in T. obliquus at 50 ng L −1 NVP concentration. Both microalgae showed varying removal efficiencies (19.53–74.56%) when exposed to NVP concentration levels of up to 4000 ng L −1 . At the late log phase (day 8), T. obliquus removed the highest percentage of NVP (74.56%), while C. tenuitheca removed 48% at an initial NVP concentration of 50 ng L −1 . Photosynthetic efficiency (Fv/Fm and rETR) of the two microalgal species, however, was not affected by environmental concentrations of NVP (up to 4000 ng L −1 ) at the mid log phase of growth. SEM analysis demonstrated that both algal species produced distinct ridges on their cell surfaces after NVP uptake. In the ecotoxicity study, the calculated IC50 values of NVP (0–100 mg L −1 ) after 96 h of exposure were 23.45 mg L −1 ( C. tenuitheca ) and 18.20 mg L −1 ( T. obliquus ). The findings of the present study may contribute to a better understanding of the environmental hazards associated with NVP and the efficacy of microalgae in removing this pharmaceutical from aquatic environments. Graphical abstract: Image 1 Highlights: Nevirapine (NVP) removal efficiency of Coelastrella tenuitheca and Tetradesmus obliquus was evaluated for the first time. No significant impact on microalgal growth and photosynthetic efficiency at environmental concentrations of NVP. The highest NVP removal of 74.56% was obtained in Tetradesmus obliquus after 8-days of cultivation. Coelastrella tenuitheca and Tetradesmus obliquus revealed 96 h IC50 of 18.20 mg L −1 and 23.45 mg L −1 for NVP, respectively.